Spontaneous acroangiodermatitis - Ipek Coban; Tuba Dilay Kokenek-Unal; Murat Alper (Wolters Kluwer Medknow Publications, 2015)
Acroangiodermatitis is a rare self-limited angioproliferative lesion which can be associated with congenital vascular malformations or acquired venous insufficiency. Despite of its benign character, differential diagnosis of this lesion is very important because it closely resembles Kaposi sarcoma. Here we present a 26-year-old male patient with unilateral, purplish-red colored papules on his right ankle which diagnosed as acroangiodermatitis and discuss histopathological features, differential diagnosis and treatment of this unusual condition.